2008
DOI: 10.1093/rheumatology/ken094
|View full text |Cite
|
Sign up to set email alerts
|

Real life experience confirms sustained response to long-term biologics and switching in ankylosing spondylitis

Abstract: Treatment of active AS with TNF blockers according to the British Society of Rheumatology guidelines leads to a sustained response for over 2 yrs with most patients tolerating the drugs well. The rate of non-response is significantly lower than that seen in RA and nearly all of these patients respond well to a second-line agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…Thirty three patients were treated with a single medication for 24 months and decreased BASDAI, BASFI and CRP values more than >20 g/dL were achieved. 5 In our study, the initial rate of concomitant DMARDs and NSAIDs at baseline was 91.52% and 54.23%, respectively. During treatment with any one of these three drugs, 23.72% of the patients discontinued DMARDs, while 10.16% discontinued NSAIDs.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…Thirty three patients were treated with a single medication for 24 months and decreased BASDAI, BASFI and CRP values more than >20 g/dL were achieved. 5 In our study, the initial rate of concomitant DMARDs and NSAIDs at baseline was 91.52% and 54.23%, respectively. During treatment with any one of these three drugs, 23.72% of the patients discontinued DMARDs, while 10.16% discontinued NSAIDs.…”
Section: Discussionmentioning
confidence: 49%
“…Due to another uveitis episode with INF, the patient was switched to ADA, which led to another uveitis episode. 5 Braun et al 32 reported that the incidence of acute anterior uveitis per 100 patient years was 15.6 in the placebo group, and 6.8 per 100 patient year in the anti-TNF group. The INF treatment was also reported to inhibit the exacerbation of uveitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations